Synthesis and X-ray characterization of 15- and 16-vertex closo-carboranes - Fangrui Zheng (Nature Portfolio, 2020)
The synthesis of closo-carboranes with more than 14 vertexes is challenging, and no examples have been reported to date. Herein, the authors present the long-sought 15- and 16-vertex closo-carboranes, in which the introduction of silyl groups to the two cage carbons is crucial; this finding might enable the synthesis of even larger carborane analogs in the future.